Traditional uses, phytochemical, pharmacology, quality control and modern applications of two important Chinese medicines from Rosa laevigata Michx.: A review - Quan, Xiao-Xiao; Huang, Yuan-Yuan; Chen, Lu; Yuan, Jing-Quan (Frontiers in Pharmacology, 2022)
Rosa laevigata Michx. is an ethnic medicine that have strong biological activities used in the traditional medicine system for the treatment of diabetes, nephropathy, myocardial damage, oxidative damage, liver damage and so on. Currently, The Chinese herb R. laevigata Michx. can be divided into two sources: Fructus R. laevigata and Radix R. laevigata, from which approximately 168 chemical components have been isolated, including triterpenoids, flavonoids, lignans, polyphenols, tannins, steroids as well as other components. Pharmacological studies have already confirmed that both of these herbs have antioxidant, anti-inflammatory, antiviral and anti-tumor activities, as well as renal protective, immunomodulatory, lipid-lowering, cardiovascular protective, bacteriostatic, and other pharmacological effects. Toxicological tests and quality control studies revealed the safety and nontoxicity of R. laevigata Michx. Therefore, this paper systematically summarizes the traditional uses, botanical, phytochemical, and pharmacology as well as the quality control and toxicology of R. laevigata Michx. and its roots, in order to provide a comprehensive reference for its continued research.